Association of Fusarium and Phomopsis with Peroba Rosa Seeds - Mazarotto,Edson José (2019)
ABSTRACT Peroba rosa (Aspidosperma polyneuron) is a native forest species endangered due to intense predatory exploitation. The objective of this study was to evaluate the association and fungi transmission in peroba rosa seeds from four regions of Paraná. Germination and vigor were evaluated using the paper roll method. Sanitary analysis consisted of the detection of endophytic and epiphytic fungi using potato-dextrose-agar medium and Fusarium selective medium. For transmission, non-disinfested seeds were sown in vermiculite and kept in greenhouse. Germination ranged from 9.3% to 60%. Fusarium sp. and Phomopsis sp. were found as epiphytic and also as endophytic. There was transmission of Fusarium sp. and Phomopsis sp. from seeds to seedlings, causing malformation and necrosis on roots and cotyledons.